Students’ Experiences in Using Online Learning Applications Due to COVID-19 in English Classroom - Sari Famularsih (Indonesia Approach Education, 2020)
The COVID-19 has brought about schools and universities closed the whole way across the world. Subsequently, teaching has changed drastically, with the distinctive rise of online learning, whereby teaching is embraced remotely and on computerized stages. Research recommends that online learning has been appeared to expand maintenance of data, and take less time, which means the progressions of coronavirus have caused may be digging in for the long haul. In this case, online learning application stages are broadly utilized by English educators in instructing and learning. The online learning stages are likewise utilized as a strengthening apparatus to advance autonomous learning. This study focuses on the utilization of online learning application in English as a Foreign Language (EFL) Classroom. The participants of this study were 35 students of second semester students of English Department in one of universities in Salatiga, Indonesia. The data was gathered through surveys and semi-structured interviews. Moreover, it was explained using descriptive qualitative approach. This investigation showed that most of students considered the utilization of online learning application in English learning is effective and efficient in this emergency situation. However, the obstacles in using online learning application in English classroom were slow-speed internet connection, so many tasks, not all teaching material can be taught through online learning, and lack of interaction between lecturer and student. In this pandemic situation, the most favorite online learning application among students is WhatsApp Group because it takes a bit of internet quota. Therefore, students can save their internet quota in this condition.